Ahab and Saul (1 Kgs 22.1-38). (June 2019) - Kim, Daewook
There are similarities between the stories of Ahab in the Book of Kings and those of Saul in the Book of Samuel which appear when examining the repetition of phrases, similar motifs, and parallel plots. The linguistic links between 1 Kings 20, 21, and 22.1-38 indicate that the stories of Ahab are juxtaposed. These similarities and juxtaposition have an effect on the interpretation of 1 Kgs 22.1-38; it is suggested that Ahab's death in 1 Kgs 22.1-38 represents YHWH's judgment on Ahab's two sins illustrated in 1 Kings 20 and 21, which constitutes a considerable parallel to Saul's two sins. Furthermore, the parallelism between Ahab's inquiry in 1 Kgs 22.1-38 and Saul's necromancy in 1 Sam. 28.3-25 reveals that Ahab's inquiry is condemned as syncretistic Yahwism, whereas the importance of YHWH's words is highlighted.